2014
DOI: 10.1007/s00289-014-1277-0
|View full text |Cite
|
Sign up to set email alerts
|

Poly(2-acrylamidoglycolic acid-co-2-acrylamide-2-methyl-1-propane sulfonic acid) and poly(2-acrylamidoglycolic acid-co-4-styrene sodium sulfonate): synthesis, characterization, and properties for use in the removal of Cd(II), Hg(II), Zn(II), and Pb(II)

Abstract: The water-insoluble polymers poly(2-acrylamidoglycolic acid-co-2-acrylamide-2-methyl-1-propane sulfonic acid) [P(AAGA-co-APSA)] and poly(2-acrylamidoglycolic acid-co-4-styrene sodium sulfonate) [P(AAGA-co-ESS)] were prepared by radical polymerization with 87.8 and 86.3 % of yield, respectively. Parameters including the water sorption capacity, effect of the pH and reaction time, maximum retention capacity of the metal ions, elution, regeneration, and selectivity were studied. The commercial resin Amberlite IRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…The maximum recovery of Pb was at pH 1.5 in the 1st stage ion exchange, which agrees with the earlier results. 18 Between pH 2.5 and 4.5, Pb recovery was constant in the range of 0.8%. Cu recovery was in the range of 43 to 45% and did not change much with pH.…”
Section: Results and Discussionmentioning
confidence: 92%
“…The maximum recovery of Pb was at pH 1.5 in the 1st stage ion exchange, which agrees with the earlier results. 18 Between pH 2.5 and 4.5, Pb recovery was constant in the range of 0.8%. Cu recovery was in the range of 43 to 45% and did not change much with pH.…”
Section: Results and Discussionmentioning
confidence: 92%
“…Consistently Morales et al . found that both poly(2‐acrylamidoglycolic acid‐co‐2‐acrylamide‐2‐methyl‐1‐propane sulfonic acid) and poly(2‐acrylamidoglycolic acid‐co‐4‐St sodium sulfonate) resins showed faster metal ion removals than that of Amberlite IRP‐64 resin, a only carboxylic group containing resin …”
Section: Resultsmentioning
confidence: 99%
“…The process of copolymerization and characterization were already studied by our investigation group [21,22]. The P(AAm-co-ESS), P(APSA-co-AAc), P(AAGA-co-APSA), and P(AAGA-co-ESS) resins were synthesized on a laboratory scale by radical polymerization using acrylamide and the hydrated sodium salt of 4-styrenesulfonate acid monomers for the P(AAm-co-ESS) resin,2-acrylamidoglyolic monohydrate acid and acrylic acid monomers for the P(APSA-co-AAc) resin,2-acrylamidoglyolic monohydrate acid and 2-acrylamide-2-methyl-1-propanesulfonic acid monomers for the P(AAGAco-APSA) resin, and 2-acrylamidoglyolic monohydrate acid and the hydrated sodium salt of 4-styrenesulfonate acid for the P(AAGA-co-ESS) resin.…”
Section: Synthesis Of Resinsmentioning
confidence: 99%
“…Our investigation group in the past already studied the synthesis and better performance ofP(AAGA-co-APSA), P(AAGA-co-ESS), P(AAm-co-ESS), and P(APSA-co-AAc) cationic ion exchange resins for remotion of metal ions from water, in comparison with the commercial resin Amberlite IRP-64 [21,22]. The aim of this research is to study the cationic ion exchange resins P(AAGA-co-APSA), P(AAGA-co-ESS), P(AAm-co-ESS), and P(APSAco-AAc) for the removal of Cr(III) from aqueous solution and to identify the optimal removal parameters using batch and column sorption-elution methods.…”
Section: Introductionmentioning
confidence: 99%